The Influence of Economic, Psychological, and Social Aspects on Financial Management Behavior Among Generation Z in DKI Jakarta: The Moderating Role of Income Characteristics - Azhany Rianda Santoso; Dwi Nastiti Danarsari (Eduvest - Journal of Universal Studies, 2025)
This study explores the influence of economic, psychological, and social aspects on the financial management behavior of Generation Z in DKI Jakarta, emphasizing the moderating role of income characteristics. A quantitative approach was employed, utilizing a survey distributed to 248 respondents, adhering to the rule of thumb of at least 10 times the number of latent variables analyzed in Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that economic factors, including financial literacy and income management, significantly impact financial behavior. Psychological factors, such as self-efficacy and self-control, also play a pivotal role, fostering prudent financial decision-making. Social influences, including familial and peer norms, were found to shape financial habits significantly. However, income characteristics as a moderating variable exhibited mixed results. While they negatively moderated the relationship between economic factors and financial behavior, no significant moderating effect was observed for psychological and social factors. These results underscore the complex interplay between intrinsic and extrinsic influences on financial management within an urban, fast-paced setting like Jakarta. The study highlights the necessity of comprehensive financial literacy programs tailored to the unique needs of Generation Z. Moreover, the findings suggest practical strategies for educators, policymakers, and financial institutions to enhance financial independence and resilience among young urban dwellers.